2012
DOI: 10.24908/pceea.v0i0.4663
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Barriers of Research Writing: Rethinking Pedagogy for Engineering Graduate Research

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Glew et al (2014) report that the majority of the respondents in their study did not have good writing skills and that they regarded writing research articles as a difficult task. The finding of the preliminary study is also supported by Rosales, Moloney, Badenhorst, Dyer and Murray (2012) who found that the majority of the participants in their study perceived that they could not express and arrange their ideas well and they were not confident in writing due to their lack of writing skill.…”
Section: Introductionsupporting
confidence: 60%
“…Glew et al (2014) report that the majority of the respondents in their study did not have good writing skills and that they regarded writing research articles as a difficult task. The finding of the preliminary study is also supported by Rosales, Moloney, Badenhorst, Dyer and Murray (2012) who found that the majority of the participants in their study perceived that they could not express and arrange their ideas well and they were not confident in writing due to their lack of writing skill.…”
Section: Introductionsupporting
confidence: 60%
“…In other papers Rosales et al 2012) we reported on data collected from the students as cohorts. In this paper, we would like to add to our analyses by focusing on one student's experience to illustrate her transformation as a graduate student writer.…”
Section: Constructions Of Deficit and Supportmentioning
confidence: 97%
“…That they continued to attend the workshop sessions despite the significant time commitment speaks to the value participants perceived in the course. Moreover, overall data analysis revealed participants' experienced growth in writing output, confidence and self-efficacy over the course of the workshop Rosales et al 2012).…”
Section: Constructions Of Deficit and Supportmentioning
confidence: 99%
“…UNAH's lax regulations in this regard have had a counterproductive effect and few students formally graduate – if ever. Gradually building students’ ability for scientific writing through both a skills and process approach (48) was a critical determinant for MEIZ completion rate.…”
Section: Lessons Learnedmentioning
confidence: 99%